2011
DOI: 10.1108/09513541111172072
|View full text |Cite
|
Sign up to set email alerts
|

Managing teacher balkanization in times of implementing change

Abstract: Purpose -The purpose of this article is to report an exploratory study which was designed to illuminate how school cultures and teachers' value orientations are affected by the educational change of parental involvement. Design/methodology/approach -The qualitative research that informs this paper is conceptualized within the interpretive paradigm. Two schools were selected purposefully for the study. In-depth interviews with 12 teachers and their principal were conducted in each school where observation took … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Qualitative studies have focused on generating thick descriptions of the relationship between different forms of school leadership, teacher practice, and curriculum change (E. Law et al, 2010;Ng, 2011;Tam, 2010). Quantitative studies have explored the practices and effects of transformational leadership (Lam, 2002;Yu et al, 2002) as well as other forms of school leadership (Pang & Pisapia, 2012;Walker & Ko, 2011).…”
Section: Downloaded By [Uq Library] At 09:36 02 November 2014mentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative studies have focused on generating thick descriptions of the relationship between different forms of school leadership, teacher practice, and curriculum change (E. Law et al, 2010;Ng, 2011;Tam, 2010). Quantitative studies have explored the practices and effects of transformational leadership (Lam, 2002;Yu et al, 2002) as well as other forms of school leadership (Pang & Pisapia, 2012;Walker & Ko, 2011).…”
Section: Downloaded By [Uq Library] At 09:36 02 November 2014mentioning
confidence: 99%
“…This group consisted of 22 articles, or 14% of the Hong Kong corpus (see Figure 5). Shaped by system implementation of a continuous series of education reforms over the past 20 years (see Y. C. Cheng & Walker, 2008), Hong Kong scholars have focused in particular on the role and contributions of leadership in the process of organizational change (e.g., Y. C. Cheng, 2000aCheng, , 2003Hallinger, 2011b;Ng, 2011;E. M. L. Wong & Li, 2008;P.…”
Section: Topical Distributionmentioning
confidence: 99%
“…Law et al (2003) found that, "[…] staff-related problems seemed to be both the most common and the worst problems for the group of principals involved in the study, regardless of the dominant values they held" (p. 508). Principals tended to view teacher competency as the most important obstacle to improving outcomes for students (Cheung and Wong, 2012;Chow, 2013;Ho and Chen, 2013;Ko et al, 2014;Lam, 2003;Law, 2011;Ng, 2011;Pang, 1998;Tan, 2014;Wong, 2003). At the same time, there is evidence to suggest that even in the emerging context of SBM, teachers' voices did not receive sufficient attention (e.g.…”
Section: Multi-level Performance Focusmentioning
confidence: 99%
“…In the second phase, there were ups and downs when parents and teachers worked together in the PTAs (Ng, 2011). For instance, two senior teachers expressed the views in the following ways:…”
Section: Another Teacher Informant Echoedmentioning
confidence: 99%